Explaining Antiretroviral Therapy Adherence Success Among HIV-Infected Children in Rural Uganda: A Qualitative Study - Olds, Peter K.; Kiwanuka, Julius P.; Ware, Norma C.; Tsai, Alexander C.; Haberer, Jessica E. (AIDS and Behavior, 2015)
High adherence is critical for achieving clinical benefits of HIV antiretroviral therapy (ART) and particularly challenging for children. We conducted 35 qualitative interviews with caregivers of HIV-infected Ugandan children who were followed in a longitudinal study of real-time ART adherence monitoring; 18 participants had undetectable HIV RNA, while 17 had detectable virus. Interviews blinded to viral suppression status elicited information on adherence experiences, barriers and facilitators to adherence, and social support. Using an inductive content analytic approach, we identified ‘lack of resources,’ ‘Lazarus effect,’ ‘caregiver’s sense of obligation and commitment,’ and ‘child’s personal responsibility’ as categories of influence on adherence, and defined types of caregiver social support. Among children with viral suppression, high hopes for the child’s future and ready access to private instrumental support appeared particularly important. These findings suggest clinical counseling should explore caregivers’ views of their children’s futures and ability to access support in overcoming adherence barriers.
Keywords: Antiretroviral therapy; Human immunodeficiency virus; Adherence; Children; Uganda